Acute effects of plyometric exercise on maximum squat performance in male athletes - Masamoto, N.; Larson, R.; Gates, T.; Faigenbaum, A. (The Journal of Strength and Conditioning Research, 2003)
This study examines the acute effects of plyometric exercise on 1 repetition maximum (RM) squat performance in trained male athletes. Twelve men (mean age ± SD: 20.5 ± 1.4 years) volunteered to participate in 3 testing sessions separated by at least 6 days of rest. During each testing session the 1RM was assessed on back squat exercise. Before all 3 trials subjects warmed up on a stationary cycle for 5 minutes and performed static stretching. Subjects then performed 5 submaximal sets of 1-8 repetitions before attempting a 1RM lift. Subjects rested for at least 4 minutes between 1RM trials. During the first testing session (T1) subjects performed a series of sets with increasing load until their 1RM was determined. During the second and third testing sessions subjects performed in counterbalanced order either 3 double-leg tuck jumps (TJ) or 2 depth jumps (DJ) 30 seconds before each 1RM attempt. The average 1RM lifts after T1 and testing sessions with TJ or DJ were 139.6 ± 29.3 kg, 140.5 ± 25.6 kg, and 144.5 ± 30.2 kg, respectively (T1 < DJ; p < 0.05). These data suggest that DJ performed before 1RM testing may enhance squat performance in trained male athletes.